TI_GERICHTE 12.2011.92 vom 12. März 2013 , Appalto - mercede - prezzi unitari indicativi - forfetizzazione - norma SIA 118 - TI Tribunale d'appello (2013)
Appalto - mercede - prezzi unitari indicativi - forfetizzazione - norma SIA 118